(untitled) (Research, Society and Development, 2022)
Tissue repair process consists in a complex and dynamic event straightly linked to tissues self-regeneration capability. In that context, it may also occur total or partial replacement of the original tissues through an extracellular matrix with significant collagen and elastin expression that results in fibroplasia. Aiming to optimizing the repair, it has been used some resources able to biomodulate the action of different kinds of tissue cells such as laser photobiomodulation (LP), light emitting diodes (LEDs), ozone therapy and plasma jet. This narrative literature review aims to describe the different phases of tissue repair and discuss about biomodulator therapies commonly applied to stimulate that process. Manuscripts discussing the proposal theme, which have been fully available were selected from Pubmed, Embase, Cochrane and Scielo database. The manuscripts must be written in English or Portuguese language, according to the exclusion and inclusion criteria designed for that study. Sixty manuscripts were selected. It may be noticed that biomodulator therapies have been used in health areas. However, studies evaluating the influence of plasma jet on tissue repair are still scarce. Preliminary results from such studies suggest that plasma jet therapy may perform important antiinflammatory, analgesic and biostimulating effects.